Determinants of non-tax revenue performance and the moderating role of internal auditors’ capability in Indonesia - Lisa Angelia; Puji Wibowo (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
Non-tax revenue (NTR) plays a crucial role in supporting Indonesia’s fiscal sustainability, yet its performance across ministries and institutions (MIs) remains uneven. This study examined the determinants of NTR performance in Indonesia’s MIs, focusing on the roles of accountability, internal control, and goods and services expenditure. It also explores whether the capability of government internal auditors moderates these relationships. Employing panel data regression on secondary data from 43 MIs over the period 2018–2023, this quantitative study integrated fixed- and random-effects models, with moderation tested via interaction terms. Results revealed that accountability and goods and services expenditure positively affected NTR performance, whereas internal control had no significant effect. Internal auditors’ capability demonstrated a statistically insignificant moderating role. These findings suggest that strengthening performance accountability systems and enhancing the effectiveness of goods and services expenditure are critical to improving service quality and optimizing NTR. Although internal control and audit capability are essential, their implementation must be strengthened to yield measurable impacts. This study advances the application of agency theory in public finance by highlighting the nuanced effects of governance variables on NTR, addressing a gap in the literature on internal audit capacity in the public sector.